Heat-insulating hollow microsphere with double-layer structure as well as preparation method and application of heat-insulating hollow microsphere

By adopting a double-layer structure of thermally insulated hollow microspheres, combined with the design of glass sphere shell layer and metal composite layer, the problems of hollow microspheres in thermal radiation control and coordinated regulation of thermal conductivity are solved, and the performance of low density, high strength and low thermal conductivity is achieved.

CN119504167APending Publication Date: 2025-02-25TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311067862.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing hollow microspheres have poor thermal radiation control capabilities and are difficult to achieve low emissivity and low thermal conductivity while maintaining a stable structure.

Method used

A thermally insulated hollow microsphere with a double-layer structure is used, and its structure is composed of a hollow core, a glass spherical shell and a metal composite layer. The metal composite layer is composed of metal sulfide regions and doped metal particles, and the internal cavity and external metal particles are formed by local vulcanization treatment.

Benefits of technology

The performance of low density, high intensity, low emissivity and low thermal conductivity is achieved, effectively solving the problems of hollow microspheres in thermal radiation control and thermal conductivity coordinated regulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504167A_ABST
    Figure CN119504167A_ABST
Patent Text Reader

Abstract

The invention discloses a heat-insulating hollow microsphere with a double-layer structure as well as a preparation method and application of the heat-insulating hollow microsphere. The heat-insulating hollow microsphere structurally comprises a hollow core, and a glass ball shell layer and a metal composite layer which are sequentially arranged from inside to outside, the metal composite layer is composed of a plurality of metal sulfide regions and metal particles doped among the metal sulfide regions; wherein in each metal sulfide region, the metal sulfide particles are gathered to form an internally hollow structure. The heat-insulating hollow microsphere has the properties of low density, high strength, low emissivity and low heat conductivity coefficient, and well solves the problem of cooperative regulation of low emissivity and low heat conductivity coefficient of the light high-strength hollow microsphere heat-insulating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of powder materials, and more specifically to a heat-insulating hollow microsphere with a double-layer structure, a preparation method and application thereof. Background Art

[0002] Facing the "dual carbon" goal, the importance of energy conservation and emission reduction has become more prominent. Specifically for energy conservation, in addition to reducing energy consumption by optimizing the characteristics of the industrial process itself, effective control of the heat transfer and dissipation of equipment and media is also an important means of saving energy. The design, controlled synthesis and application of high-efficiency thermal insulation materials are important starting points and supporting technologies in the field of energy conservation. For the transmission and diffusion of heat, heat conduction, heat convection and heat radiation are the main methods. At present, cavity structures are mostly used in the research of thermal insulation materials to control gas convection and reduce convective heat transfer. At the same time, different forms of cavity structures (such as large-sized closed hollow cores inside the material, porous channels of different scales, etc.) will also reduce the content of effective substances with high thermal conductivity that contributes relatively large to heat conduction, and extend the heat transfer path, thereby increasing thermal resistance and reducing the overall thermal conductivity of the material. At present, a variety of hollow or porous structures of inorganic (such as inorganic salts, oxides, etc.) or organic materials (usually polymers) have been used for the study of high-efficiency thermal insulation. Its specific cavity structure can be an open or closed cavity or channel, and the macroscopic application form is mostly powder filling, thermal insulation coating or thermal insulation board. Relatively speaking, closed cavities have greater suppression of thermal convection and tolerance to environmental factors (such as moisture adsorption leading to performance degradation), and have more advantages in long-term service.

[0003] Hollow microsphere structure is a typical type of cavity structure. Its spherical shape gives it excellent fluidity and filling properties, making it easy to use as a filler to prepare composite materials or as a powder to be used independently. In particular, hollow microspheres with a closed cavity structure (dense spherical shell) have received widespread attention due to their high structural and performance stability. The reason is that high stability is conducive to the long-term effective maintenance of thermal insulation performance, while high mechanical strength (structural stability under mechanical environment) is conducive to its application in the design of structural-functional integrated materials. However, similar to other types of hollow or porous materials, although ordinary hollow microspheres can control heat conduction and heat convection through their large-proportion cavity and thin-wall structure, their ability to control (block) thermal radiation is poor. The control of thermal radiation usually requires the use of low-emissivity materials, and metals are common low-emissivity materials. Therefore, combining the hollow microsphere structure with metal materials is expected to obtain composite hollow microspheres with low density, structural strength and high thermal insulation performance. However, metal materials usually have a much higher thermal conductivity than polymers, inorganic salts and oxides, which makes solid thermal conductivity too strong and difficult to achieve coordinated optimization of thermal conduction and thermal radiation. Existing structural design and implementation methods for hollow microspheres and metal composites also make it difficult to simultaneously achieve low emissivity and thermal conductivity while maintaining a stable hollow spherical structure. Summary of the invention

[0004] Based on the above problems, one object of the present invention is to provide a thermal insulation hollow microsphere with a double-layer structure and a preparation method and application thereof. The thermal insulation hollow microsphere has the properties of low density, high strength, low emissivity and low thermal conductivity, which well solves the problem of coordinated regulation of low emissivity and low thermal conductivity of lightweight and high-strength hollow microsphere thermal insulation materials.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] On the one hand, the present invention provides a heat-insulating hollow microsphere with a double-layer structure, wherein the structure of the heat-insulating hollow microsphere comprises a hollow core, and a glass shell layer and a metal composite layer arranged in sequence from the inside to the outside;

[0007] The metal composite layer is composed of a plurality of metal sulfide regions and metal particles doped between the metal sulfide regions; wherein, in each metal sulfide region, the metal sulfide particles are aggregated to form a hollow structure.

[0008] Furthermore, the metal particles have the same metal element as the metal sulfide particles.

[0009] Furthermore, the metal element in the metal particles and metal sulfide particles is selected from one of nickel, cobalt, iron and copper.

[0010] The interior of the heat-insulating hollow microsphere of the present invention is a large-scale continuous cavity, the middle is a glass spherical shell, and the outer side is a composite of a small-sized sulfide cavity and a metal. The glass spherical shell is a closed continuous shell that provides mechanical support for the entire structure; the outer spherical shell is a loosely distributed metal sulfide particle hollow microsphere and metal particles. The cavities of different sizes and distribution states inside the microsphere and on the outer spherical shell give the hollow microsphere a lower thermal conductivity, and the presence of the outer metal particles reduces the emissivity of the microsphere.

[0011] Furthermore, in terms of weight percentage, the heat insulating hollow microspheres contain 35-75wt% of glass shell layer, 15-35wt% of metal sulfide particles and 5-30wt% of metal particles.

[0012] Furthermore, in terms of weight percentage, the content of the glass shell layer in the insulating hollow microspheres includes but is not limited to 35-60wt%, 40-60wt%, 45-60wt%, 50-60wt%, 55-60wt%, etc.

[0013] Furthermore, in terms of weight percentage, the content of metal sulfide particles in the heat insulating hollow microspheres includes but is not limited to 16-35wt%.

[0014] Furthermore, in terms of weight percentage, the content of metal particles in the heat insulating hollow microspheres includes but is not limited to 10-30wt%, 11-30wt%, etc. Furthermore, the density of the heat insulating hollow microspheres is 0.3-0.9g / cm 3 , the average diameter is 10-80μm.

[0015] In another aspect, the present invention provides a method for preparing the above-mentioned heat-insulating hollow microspheres, comprising the following steps:

[0016] Directed assembly of metal oxide spherical shells on the surface of glass hollow microspheres to obtain microspheres A;

[0017] The microsphere A is subjected to local vulcanization treatment on the surface to obtain the heat insulating hollow microsphere.

[0018] Furthermore, the glass hollow microspheres are subjected to flotation treatment before use, which specifically includes:

[0019] The glass hollow microspheres are immersed in a flotation liquid, the floating glass hollow microspheres are collected, and the floating glass hollow microspheres are dried to obtain the flotation-treated glass hollow microspheres.

[0020] Furthermore, the hollow glass microspheres are hollow microspheres with silicate glass shells. They can be purchased from commercial sources or prepared by methods known in the art. There is no particular limitation on the structural dimensions of the hollow glass microspheres with silicate glass shells, which are suitable for the purpose of the invention of this application. Meanwhile, the thickness of the silicate shells can be 0.3-2 μm.

[0021] Furthermore, the ratio of the glass hollow microspheres to water in the flotation treatment is 1:10-1:3.

[0022] Furthermore, the method for directional assembly of metal oxide spherical shells on the surface of glass hollow microspheres comprises the following steps:

[0023] The glass hollow microspheres are mixed with the reaction solution and reacted in an air atmosphere to obtain microspheres A having a glass / metal oxide double spherical shell;

[0024] Wherein, the reaction temperature is 400-600°C, the reaction time is 30-240min, preferably 60min;

[0025] The reaction solution consists of metal salt, water-soluble organic matter and water;

[0026] The metal salt is selected from nitrates or organic acid salts of the metal;

[0027] The water-soluble organic matter is selected from one or more of sucrose, starch and citric acid;

[0028] The mass ratio of the glass hollow microspheres to the metal salt, the water-soluble organic matter and water is 2:10-15:4-5:3-5.

[0029] Further, the reaction temperature includes but is not limited to 400-550°C, 400-500°C, 400-450°C, 450-600°C, 450-550°C, 450-500°C, 500-600°C, 500-550°C, 550-600°C, 600°C, etc.

[0030] Furthermore, the method further comprises a step of sieving after the reaction. The sieving method is: the product obtained by the reaction is gently ground, pressed and dispersed on a 50-300 mesh standard sieve and passed through the sieve holes.

[0031] Furthermore, the method of performing localized vulcanization treatment on the surface of microsphere A comprises the following steps:

[0032] The microsphere A is mixed with sublimated sulfur and subjected to heat treatment in a reducing atmosphere to obtain the heat insulating hollow microsphere;

[0033] Wherein, the heat treatment temperature is 450-600°C, and the time is 3-10h, preferably 5h.

[0034] Furthermore, the temperature of the heat treatment includes but is not limited to 450-550°C, 450-500°C, 500-600°C, 500-550°C, 550-600°C, 600°C, 550°C, 500°C, 450°C, etc.

[0035] Furthermore, the mass ratio of the microsphere A to the sublimated sulfur is 5:4-9:2.

[0036] Furthermore, the reducing atmosphere is hydrogen or a mixture of hydrogen and argon.

[0037] Furthermore, the density of the glass air microspheres includes but is not limited to 0.2-0.8 g / cm 3 , 0.2-0.6g / cm 3 , 0.2-0.5g / cm 3 , 0.25-0.8g / cm 3 , 0.25-0.6g / cm 3 , 0.25-0.5g / cm 3 , 0.3-0.8g / cm 3 , 0.3-0.6g / cm 3 , 0.3-0.5g / cm 3 , 0.3g / cm 3 , 0.38g / cm 3 , 0.46g / cm 3 The obtained heat insulating hollow microspheres have low density, high strength, low emissivity and low thermal conductivity.

[0038] Furthermore, the method further comprises a step of screening after the heat treatment. The screening method is: the product obtained by the heat reaction is gently ground, pressed and dispersed on a 50-300 mesh standard sieve and passes through the sieve holes.

[0039] The preparation method is simple and easy to implement; the layers of the heat-insulating hollow microspheres prepared by the preparation method are firmly bonded to each other, and the structure of the heat-insulating hollow microspheres is stable and regular.

[0040] In yet another aspect, the present invention provides use of the thermal insulating hollow microspheres as described above in thermal insulating powders and thermal insulating fillers.

[0041] The beneficial effects of the present invention are as follows:

[0042] The heat-insulating hollow microspheres provided in the present invention achieve lower overall density and lower thermal conductivity of the hollow microspheres through the internal cavity; the outer spherical shell is composed of hollow metal sulfide particles and metal particles, the former can reduce the overall thermal conductivity of the microspheres, and the latter can reduce the overall infrared emissivity of the microspheres; the unique double hollow structure (hollow cavity of the microsphere as a whole + hollow cavity of the metal sulfide structural unit of the outer spherical shell) and the combination of metal island-shaped (non-interconnected) structural units reduce the infrared emissivity while avoiding a significant increase in thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0044] Figure 1 The schematic diagram of the structure of the heat insulating hollow microspheres in the present invention is shown.

[0045] Figure 2 A schematic diagram of the preparation process of the heat insulating hollow microspheres of the present invention is shown.

[0046] Figure 3 A low-magnification SEM image of the hollow microspheres prepared in Example 3 is shown.

[0047] Figure 4 A high-magnification SEM image of the hollow microspheres prepared in Example 3 is shown.

[0048] Figure 5 A locally enlarged SEM image of the hollow microspheres prepared in Example 3 is shown.

[0049] Figure 6 The X-ray diffraction pattern of the hollow microspheres prepared in Example 5 is shown. DETAILED DESCRIPTION

[0050] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0051] In a specific embodiment of the present invention, the structural schematic diagram of the obtained heat insulating hollow microspheres is as follows Figure 1 The schematic diagram of its preparation process is shown in Figure 2 shown.

[0052] from Figure 2It can be seen that process A is the process of directional assembly of metal oxide shells on the surface of glass hollow microspheres; process B is to perform localized sulfurization treatment on the surface of microsphere A to obtain the insulating hollow microspheres. Process B specifically includes B1: forming metal sulfide particles on the surface of metal oxide, and B2: forming cavities inside the metal sulfide particles and external metal particles.

[0053] Example 1

[0054] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0055] The density is 0.46g / cm 3 Commercial glass hollow microspheres.

[0056] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0057] (2) 10 g of cobalt nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0058] (3) 2 g of hollow microsphere A was mixed with 12 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0059] (4) The hollow microspheres B obtained in step (3) were mixed with 1.4 g of sublimed sulfur, and heat treated at 500° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the insulating hollow microspheres.

[0060] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.6%, 22.3% and 22.1% respectively. Other structural and performance parameters are shown in Table 1.

[0061] In this specific implementation, the performance test method of the thermal insulation hollow microspheres is as follows:

[0062] 1) Density is tested using Archimedes principle;

[0063] 2) The strength is evaluated by isostatic pressing treatment, and the test is carried out according to the patent "A method for determining the isostatic strength of hollow glass microspheres" (201410196976.0);

[0064] 3) Thermal conductivity is tested using a thermal constant analyzer;

[0065] 4) The emissivity is tested using an infrared emissivity tester.

[0066] Example 2

[0067] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0068] The density is 0.38g / cm 3 Commercial glass hollow microspheres.

[0069] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0070] (2) 10 g of cobalt nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0071] (3) 2 g of hollow microsphere A was mixed with 12 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0072] (4) The hollow microspheres B obtained in step (3) were mixed with 1.4 g of sublimed sulfur, and heat treated at 500° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the insulating hollow microspheres.

[0073] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.5%, 22.3% and 22.2% respectively. Other structural and performance parameters are shown in Table 1.

[0074] Example 3

[0075] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0076] The density is 0.38g / cm 3 Commercial glass hollow microspheres.

[0077] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0078] (2) 10 g of cobalt nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0079] (3) 2 g of hollow microsphere A was mixed with 12.8 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0080] (4) The hollow microspheres B obtained in step (3) were mixed with 1.1 g of sublimed sulfur, and heat treated at 500°C for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the heat-insulating hollow microspheres. The low-magnification SEM, high-magnification SEM, and local magnification SEM images are shown in FIG. Figure 3 , Figure 4 and Figure 5 As shown in the figure, we can see the complete microspheres, metal and sulfide composite spherical shells, and the cavities inside the sulfide structural units. Figure 6 As shown, curve a is the diffraction curve of the glass-oxide intermediate, where a relatively pure oxide crystal phase can be seen; curve b is the diffraction curve of the final product, where clear crystal diffraction peaks corresponding to the metal and sulfide structural units can be seen.

[0081] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.5%, 16.7% and 27.8% respectively. Other structural and performance parameters are shown in Table 1.

[0082] Example 4

[0083] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0084] The density is 0.38g / cm 3 Commercial glass hollow microspheres.

[0085] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0086] (2) 10 g of cobalt nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0087] (3) 2 g of hollow microsphere A was mixed with 10.7 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0088] (4) The hollow microspheres B obtained in step (3) were mixed with 2.3 g of sublimated sulfur, and heat treated at 500° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the insulating hollow microspheres.

[0089] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.7%, 33.2% and 11.1% respectively. Other structural and performance parameters are shown in Table 1.

[0090] Example 5

[0091] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0092] The density is 0.30g / cm 3 Commercial glass hollow microspheres.

[0093] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0094] (2) 13 g of ferric nitrate, 4 g of citric acid and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0095] (3) 2 g of hollow microsphere A was mixed with 15.5 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0096] (4) The hollow microspheres B obtained in step (3) were mixed with 1.1 g of sublimed sulfur, and heat treated at 600° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the insulating hollow microspheres.

[0097] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.4%, 16.6% and 28% respectively. Other structural and performance parameters are shown in Table 1.

[0098] Example 6

[0099] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0100] The density is 0.25g / cm 3 Commercial glass hollow microspheres.

[0101] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0102] (2) 13 g of copper nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0103] (3) 2 g of hollow microsphere A was mixed with 8.2 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0104] (4) The hollow microspheres B obtained in step (3) were mixed with 1.0 g of sublimed sulfur, and heat treated at 550° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the insulating hollow microspheres.

[0105] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.5%, 16.8% and 27.7% respectively. Other structural and performance parameters are shown in Table 1.

[0106] Example 7

[0107] A preparation method of heat-insulating hollow microspheres, the specific implementation scheme is as follows:

[0108] The density is 0.20g / cm 3 Commercial glass hollow microspheres.

[0109] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0110] (2) 10 g of nickel nitrate, 4 g of citric acid and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain a treatment solution A;

[0111] (3) 2 g of hollow microsphere A was mixed with 12.8 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0112] (4) The hollow microspheres B obtained in step (3) were mixed with 1.1 g of sublimed sulfur, and heat treated at 450° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, the insulating hollow microspheres.

[0113] The mass percentages of the glass shell layer, metal sulfide particles and metal particles in the heat insulating hollow microspheres obtained in this example are 55.5%, 16.7% and 27.8% respectively. Other structural and performance parameters are shown in Table 1.

[0114] Comparative Example 1

[0115] A glass / metal hollow composite microsphere preparation, the specific implementation scheme is as follows:

[0116] The density is 0.38g / cm 3 Commercial glass hollow microspheres.

[0117] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0118] (2) 10 g of cobalt nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0119] (3) 2 g of hollow microsphere A was mixed with 12.8 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0120] (4) The hollow microspheres B obtained in step (3) are heat treated at 500° C. for 8 h in a 5% H2-95% Ar atmosphere, and after cooling, dispersed through an 80-mesh sieve to obtain the target product, glass / metal hollow composite microspheres.

[0121] The mass percentages of glass and metal in the glass / metal hollow composite microspheres obtained in this comparative example are 58.7%, 1% and 41.3% respectively. Other structural and performance parameters are shown in Table 1.

[0122] Comparative Example 2

[0123] A glass / metal sulfide hollow composite microsphere preparation, the specific implementation scheme is as follows:

[0124] The density is 0.38g / cm 3 Commercial glass hollow microspheres.

[0125] (1) Flotation of glass hollow microspheres: glass hollow microspheres and water were mixed at a volume ratio of 1:4, stirred, allowed to stand for stratification, and then the upper floating microspheres were collected, filtered, and dried to obtain hollow microspheres A;

[0126] (2) 10 g of cobalt nitrate, 4 g of sucrose and 3 g of water were mixed in a beaker, heated in a water bath at 45° C., and magnetically stirred until completely dissolved to obtain treatment solution A;

[0127] (3) 2 g of hollow microsphere A was mixed with 3.7 g of treatment solution A, and then treated at 600° C. for 60 min in an air atmosphere. After the reaction, the mixture was dispersed through an 80-mesh sieve to obtain hollow microsphere B;

[0128] (4) The hollow microspheres B obtained in step (3) were mixed with 1.1 g of sublimed sulfur, and heat treated at 500° C. for 5 h in a 5% H2-95% Ar atmosphere. After cooling, the mixture was dispersed through an 80-mesh sieve to obtain the target product, glass / metal sulfide-metal hollow composite microspheres.

[0129] The mass percentages of glass and metal sulfide in the glass / metal sulfide hollow composite microspheres obtained in this comparative example are 76.8% and 23.2% respectively. Other structural and performance parameters are shown in Table 1.

[0130] Table 1

[0131]

[0132]

[0133] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A heat-insulating hollow microsphere with a double-layer structure, characterized in that: The structure of the heat insulating hollow microsphere comprises a hollow core, a glass shell layer and a metal composite layer arranged in sequence from the inside to the outside; The metal composite layer is composed of a plurality of metal sulfide regions and metal particles doped between the metal sulfide regions; wherein, in each metal sulfide region, the metal sulfide particles are aggregated to form a hollow structure.

2. The heat insulating hollow microsphere according to claim 1, characterized in that: The metal particles are the same metal element as the metal sulfide particles; and / or The metal element in the metal particles and metal sulfide particles is selected from one of nickel, cobalt, iron and copper.

3. The heat insulating hollow microsphere according to claim 1, characterized in that: Calculated by weight percentage, the heat insulating hollow microspheres contain 35-75wt% of glass sphere shell layer, 15-35wt% of metal sulfide particles and 5-30wt% of metal particles.

4. The heat insulating hollow microsphere according to claim 1, characterized in that: The density of the insulating hollow microspheres is 0.3-0.9 g / cm 3 , the average diameter is 10-80μm.

5. The method for preparing the heat insulating hollow microspheres according to any one of claims 1 to 4, characterized in that: The steps include: Directed assembly of metal oxide spherical shells on the surface of glass hollow microspheres to obtain microspheres A; The microsphere A is subjected to local vulcanization treatment on the surface to obtain the heat insulating hollow microsphere.

6. The preparation method according to claim 5, characterized in that: The method for directional assembly of metal oxide spherical shells on the surface of glass hollow microspheres comprises the following steps: The glass hollow microspheres are mixed with the reaction solution and reacted in an air atmosphere to obtain microspheres A having a glass / metal oxide double spherical shell; Wherein, the reaction temperature is 400-600°C and the reaction time is 30-240min; The reaction solution consists of metal salt, water-soluble organic matter and water; The metal salt is selected from nitrates or organic acid salts of the metal; The water-soluble organic matter is selected from one or more of sucrose, starch and citric acid; The mass ratio of the glass hollow microspheres to the metal salt, the water-soluble organic matter and water is 2:10-15:4-5:3-5.

7. The preparation method according to claim 5, characterized in that: The method for performing localized vulcanization treatment on the surface of microsphere A comprises the following steps: The microsphere A is mixed with sublimated sulfur and subjected to heat treatment in a reducing atmosphere to obtain the heat insulating hollow microsphere; Wherein, the heat treatment temperature is 450-600°C and the time is 3-10h.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the microsphere A to the sublimated sulfur is 5:4-9:

2.

9. The preparation method according to claim 7, characterized in that: The reducing atmosphere is hydrogen or a mixture of hydrogen and argon.

10. Use of the insulating hollow microspheres according to any one of claims 1 to 4 in powder insulation and insulating fillers.

Citation Information

Patent Citations

  • Method for measuring isostatic pressure resistance of hollow glass beads

    CN103954506A